Characterization of a collection of Aeschynomene histrix in subhumid Nigeria - Merkel, U; Peters, Michael; Schultze-Kraft, Rainer; Berner, D.K. (Cambridge University Press, 2000)
A collection of 64 accessions of the South American pasture legume Aeschynomene histrix Poiret was characterized in 1995 at Ibadan in south-west Nigeria in order to test the potential of the accessions as forage plants in subhumid areas and as a trap crop for the parasitic plant Striga hermonthica (Del.) Benth. All accessions had a low biomass production during the first 8 weeks after sowing but soon variations in the collection became apparent. Morphologically, accessions could be classified as having prostrate, decumbent, semi-erect and erect growth habit. The semi-erect to erect accessions grew vigorously and had high dry matter yields. The most frequent disease was Rhizoctonia foliar blight, for which, in general, prostrate accessions had a higher severity. In contrast, plants with semi- erect to erect growth habit were more susceptible to a wilting disease probably caused by Fusarium spp. With an average crude protein content of 16% and 48-h in sacco dry matter and protein digestibilities of c. 50%, fodder quality of 13-week-old plants was similar to that of other tropical forage legumes. As a result of a laboratory experiment to test the potential of A. histrix to act as a trap crop for Striga hermonthica, 13 accessions showing a significant influence on in vitro Striga hermonthica seed germination were identified. Twenty promising accessions were selected for further evaluation. These accessions showed good biomass production and/or high tolerance to diseases and/or significant influence on Striga hermonthica seed germination. Such material has the potential to contribute to both livestock-forage and improved fallow systems with the aim of increasing the sustainability of agricultural production in West Africa.